PENGARUH TENAGA KERJA, BAHAN BAKU TERHADAP PRODUKTIVITAS DAN PENDAPATAN USAHA INDUSTRI KAIN BATIK KOTA DENPASAR - Permana, I Komang Aditya; Widanta, A.A Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
The batik industry in Denpasar City period 2014-2018 saw decrease in labor productivity, and this decrease in labor productivity will have an impact on total production, production costs and company revenues. The purpose this study to analyze effect of labor and raw materials on productivity and business income. The samples was 57 business units, with the Proportional Random Sampling technique. Data collection was carried out through non-behavioral observation and structured interviews. The analysis technique used is the path analysis technique. Based on the analysis, it was found that labor and raw materials had a positive and significant effect on business productivity in the batik cloth industry in Denpasar City. Labor, raw materials and productivity have a positive and significant effect on business income in the batik cloth industry in Denpasar City. Labor and raw materials have a significant effect on income through productivity in the batik fabric industry in Denpasar City. It is recommended that the batik cloth industry in Denpasar City be able to increase the use of labor and raw materials that can increase productivity and income, while coordination is needed between local governments in order to make policies related to this.   Keywords: labor, raw materials, productivity, income